Optimization of the process of working-in details of gear pumps connections after repair - Viunyk, Olha; В’юник, Ольга Володимирівна; Plakhotnyk, I. (Запоріжжя : 2022, 2022)
EN: Working-in of friction pairs is a mandatory technological process, which is of great importance for wear-resistant surfaces and, as a result, extending the service life of hydraulic transmissions. It is a complex process that takes place under the influence of a large number of different factors. The entire working-in process can be divided into three periods: - the first is characterized by increased initial wear (during this period, the quality of the surface of the friction pairs is optimized); - the second is characterized by a decrease in the amount of wear, a decrease in mechanical losses due to friction, strengthening of surfaces, geometric alignment of parts relative to each other; - the third is characterized by the stabilization of all the main indicators of axial-piston units: wear of parts, feed rate, mechanical losses, oil pressure, temperature, etc.
Viunyk O. V., Plakhotnyk I. Optimization of the process of working-in details of gear pumps connections after repair. Технічне забезпечення інноваційних технологій в агропромисловому комплексі : матеріали IV Міжнар. наук.-практ. Інтернет-конференції (Запоріжжя, 01-25 листопада 2022 р.). Запоріжжя : ТДАТУ, 2022. С. 183-184.